Changes in patient recruitment parameters and their derivatives under the influence of external factors – population size and density of residence in a certain area - S. S. Milovanov (Фармакоэкономика)
Background. The lack of targeted patient recruitment for clinical trials reaches 90%, which leads to failures of a trial as a whole and insufficient access to the necessary treatment or diagnostic method for patients. To find out the reasons for recruitment failures, many factors are considered, the action of which is difficult to assess due to high variability. In general, various factors are named that reduce patient recruitment, while factors that improve it are much less known.Objective: to investigate changes in the parameters and indicators of patient recruitment for clinical trials depending on the influence of external factors.Material and methods. A retrospective analysis of four international multicenter clinical trials of phases II–III was performed by 16 patient recruitment parameters and their 6 derivatives (indicators) – both widely used in the literature and newly proposed. A total of 622 patients from 70 clinical centers located in 59 cities of Russia, Ukraine, and Belarus were included in the study. The methods of descriptive statistics and typing were used. To study the influence of factors, internal and external factors were selected, external factors including population size, area and density of residence were analysed, and changes in parameters and indicators depending on the influence of each factor were examined. The area and population density were studied in inseparable connection with each other.Results. A simple classification of factors was proposed – external and internal to the clinical center where patients were recruited. The factors classified as external were analyzed depending on the change in the proposed parameters of patient recruitment for clinical trials and their relationships – indicators (derivatives). The final rate of patient recruitment and the final number of patients recruited in the population group of 1–2 million people had statistically significant (p<0.05) higher values (0.57±0.20 and 15.08±5.06, respectively) than in group with up to 1 million people – 0.14±0.05 and 3.75±1.24.Conclusion. For the first time, an extended panel of parameters and indicators that allow evaluating the influence of various factors on patient recruitment for clinical trials was proposed. The value of the proportion of parameters and indicators that had statistical differences among themselves in the group influenced by the population size factor was more than twice as large as the proportion of similar parameters and indicators in the group influenced by area and population density: 47% and 23%, respectively, which may indicate more strong influence of the first factor.